2019
DOI: 10.1007/s40430-019-1863-z
|View full text |Cite
|
Sign up to set email alerts
|

Bionic optimum design of straight cone nozzle and the effectiveness evaluation of reducing fluid resistance

Abstract: High-pressure water jet technology is a clean and effective approach to break, cut or clean solid materials. The nozzle's hydraulic performance determines the efficiency and quality of the high-pressure water jet technology implementation. The fluid resistance reduction technology of bionic non-smooth surface is applied to the structural design of the straight cone nozzle successfully. The circular groove is selected as the bionic unit. The selection results in the investigation and development of a bionic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…All the optimization work involves increasing rock breaking effect, saving hydraulic energy, and improving energy conversion efficiency [20,21]. Wen et al [22] chose a circular annular groove as a bionic unit and arranged the circular annular groove evenly on the inner cavity surface of a straight cone nozzle. The original smooth flow channel inside the nozzle became a bionic non-smooth surface structure, effectively improving the flow channelʹs hydraulic characteristics inside the nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…All the optimization work involves increasing rock breaking effect, saving hydraulic energy, and improving energy conversion efficiency [20,21]. Wen et al [22] chose a circular annular groove as a bionic unit and arranged the circular annular groove evenly on the inner cavity surface of a straight cone nozzle. The original smooth flow channel inside the nozzle became a bionic non-smooth surface structure, effectively improving the flow channelʹs hydraulic characteristics inside the nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the lateral deflection of peak pressure was affected by the combination of jet velocity, surface shape, and surface angle. Weng et al [14] designed circular grooves with different widths and numbers at the nozzle inlet. The liquid support effect produced by the circular grooves reduced the resistance between the water jet and the inner surface of the nozzle and improved the impact force of the water jet.…”
Section: Introductionmentioning
confidence: 99%